3
 
ALGEBRA
  Percent increase or decrease
  Denoting:  base (x), amount (y), percent (p) and where (x + y) denotes an original or base value x increased (+) or decreased (- ) by amount y, using proportions
x : 100 = (x + y) : (100 + p    and    y : p = (x + y) : (100 + p)
Example:  In the price of $33 included is tax of 10%. What is net price? 
 
Example:  A price reduced by 20% amounts $330, how much is reduced?
 Polynomial and/or polynomial functions and equations
A polynomial (in a variable x) is a function or an expression written in standard form
 f (x) = anxn + an -1xn -1 + an -2xn -2 + . . . + a2x2 + a1x + a0
where,  an, an -1, . . . , a2, a1, a0  are real numbers called coefficients. If an is non-zero, polynomial is of degree n (n is a natural number).
  Addition and subtraction of polynomials 
 If    g (x) = bmxm + bm -1xm -1 + . . . + b2x2 + b1x + b0   then for m = n,
 f (x) + g (x) = (an + bn)xn + (an -1 + bn -1)xn -1 + . . . + (a2 + b2)x2 + (a1 + b1)x + (a0 + b0)
Example:  Given  f (x) = - x3 + 2x2 - 3x +    and    g (x) = 2x4 - 5x3 + x - 4  then
   f (x) - g (x) = (0 - 2)x4 + (-1 - 5)x3 + (2 - 0)x2 + (- 3 - 1)x + (1 + 4)
                                         = - 2x4 + 4x3 + 2x2 - 4x + 5
 Multiplication of polynomials 

We multiply polynomials using the distributive law and the commutative and associative laws of multiplication and addition.

Example:  Given are polynomials,  f (x) = - 2x3 + 4x -   and   g (x) = x2 + 3x - 4  then
                 f (x) g (x) = (- 2x3 + 4x - 1) (x2 + 3x - 4)
                                   = - 2x5 + 4x3 - x2 - 6x4 + 12x2 - 3x + 8x3 - 16x + 4
                                   = - 2x5 - 6x4 + 12x3 + 11x2 - 19x + 4
 Division of polynomials 
Dividing two polynomials,  p (x) and  q (x), obtained is quotient Q (x) and remainder R (x) related by 
p (x) = Q (x) q (x) + R (x).
The two polynomials are divisible if  R (x) = 0. 
Example: Given,  f (x) = 3x3 - 10x2 + 11x - and g (x) = x2 - 2x  + 1, find  Q (x) =  f (x) g (x).
 therefore,   3x3 - 10x2 + 11x - 4 = (3x -  4) (x2 - 2x  + 1)  and   R (x) = 0.
Example:  Given,  f (x) = x3  + 2x  and  g (x) = - x2  + x  + 1,  find quotient  f (x) g (x).
 thus,   x3 + 2x = (- x - 1) ( - x2 + x  + 1) + 4x  + 1  i.e.,  Q (x) = - x - and  R (x) = 4x  + 1.
 
 
 
 
 
 
Contents A
 
 
 
 
Copyright 2004 - 2020, Nabla Ltd.  All rights reserved.